Application of mixed bone graft (autograft + allograft) in the management of giant cell tumor of bone - Datta, NK; Ahamed, SU; Miah, MM; Nessa, A (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):225-31. The abstract of this article is available on the PubMed website